Implementation of Policies on Law Enforcement in Money Laundering Cases in Indonesia and Denmark - Magfirah, Altingia; Waluyo, Waluyo (HUKUM PEMBANGUNAN EKONOMI, 2023)
Money laundering is a serious crime, this crime can occur in several jurisdictions, so it can be said to be a transnational crime. Money laundering as one of the crimes committed by a group of people or more than one person. This form of money laundering is in the form of a criminal offense, while the original crime is often called a predicate offense. Some of the motivating reasons for committing money laundering crimes are that the money is used as capital as a business or sent to non-banking financial service providers such as insurance. The impact of money laundering will disrupt the national and international economy. In addition to these impacts, money laundering will result in disruption of the operational effectiveness of the economic system which will later lead to bad economic policies, especially in certain countries. Money laundering practices can also destabilize the national economy because money laundering causes sharp fluctuations in interest rates and exchange rates. The problem of money laundering will never run out even though the development of this case from year to year is increasing both in a number of state losses and its modus operandi. This study aims to see the implementation of policies on money laundering cases in Indonesia and will be compared with Denmark so that it can find out the implementation of each country's policies and what obstacles the Indonesian state faces in eradicating money laundering crimes. So the author is interested in giving the title of this study as Implementation of policies on law enforcement in money laundering cases in Indonesia and Denmark. The legal research used is qualitative research which is included in the category of normative research. The data used is secondary data.